Information Economy Report 2015 - United Nations Conference on Trade; Development (United Nations, 2015)
Electronic commerce (e-commerce) is rapidly transforming the way in which enterprises are interacting among each other as well as with consumers and governments. Despite important potential benefits, businesses and consumers in developing countries were for a long time slow to exploit e-commerce. As a result of changes in the evolving landscape for information and communications technologies (ICTs), this pattern is now changing, and e-commerce is growing rapidly in emerging markets and developing economies. Against this background, this publication revisits the potential opportunities and risks of e-commerce and examines how countries can benefit the most from the phenomenon in today's Information Society. Using official statistics and private sector data, it provides an up-to-date review of global and regional trends related to e-commerce in view of changes in the ICT landscape, focusing on developing countries while drawing lessons from developed countries.